Adverse effects of captopril in hospital outpatients with hypertension. Issue 772 (February 1990) - Walley, T.; Winstanley, P.; Roberts, D.; Grimmer, M.; Orme, M.; Breckenridge, A.
Abstract : Hypertensive patients prescribed captopril while attending a hospital hypertension clinic were studied, to identify the benefits of the drug, its adverse effects and factors predisposing to them. One hundred and eighty two patients were followed for a mean of 18 months; 24 received captopril alone, and 158 combinations of captopril and other antihypertensive drugs, especially loop diuretics (91/158), or thiazide diuretics (57/158), or other vasodilators (57/158). The mean final dose of captopril was 67 mg/day. Blood pressure (BP) was effectively controlled in 73% of patients (mean fall in systolic BP 29 mmHg, CI 24 to 34, P less than or equal to 0.001; mean fall in diastolic BP 18 mmHg, CI 16 to 20, P less than or equal to 0.001). Blood urea and creatinine rose slightly in all patients (urea by 0.9 mmol/l [13%], CI 0.5-1.3, P less than or equal to 0.001 and creatinine by 9 mumols/l [8%], CI 4-13, P less than or equal to 0.001). Twenty six patients were withdrawn from captopril therapy: 6 because of poor control of their blood pressure, two because it was no longer necessary and 12 (7.7%) because of extrarenal adverse effects--10 for rashes, one each for gastric upset and impotence. Captopril was withdrawn in a further 6 patients, because of deteriorating renal function. Factors discriminating those at risk of renal dysfunction were high doses of captopril, concomitant high dose diuretic therapy and undiagnosed renovascular disease.